Assets bubbles, unemployment, and financial market frictions - Ken-ichi Hashimoto; Ryonghun Im; Takuma Kunieda; Akihisa Shibata (Osaka University, Institute of Social and Economic Research (ISER), 2020)
A tractable model with infinitely lived agents is constructed for the examination of bubbles and unemployment. It is demonstrated that the presence of bubbles stimulates capital accumulation and reduces unemployment. The presence of bubbles also changes the effects of government policies that target unemployment and welfare conditions in the labor market. The main findings are as follows: (i) the presence of bubbles is more beneficial to an economy with severe credit constraints; (ii) the presence of bubbles mitigates the negative effects of taxation and unemployment benefits on unemployment and welfare; and (iii) these mitigation effects decrease as credit constraints are relaxed.
Keywords: J64; O41; O42; 330; Asset bubbles; Unemployment; Labor-market matching frictions; Financial frictions